5 - Quelle Stratégie de Développement pour l’Afrique Sub-Saharienne: by Hervé Diata - Hervé Diata (Africa Development, 1990)
Summary: Beyond the reaction to the Sub-Saharan African economic decline, including optimism for some and pessimism for others, the present debate on the development problematic and alternatives is based on the opposition between two paradigms: one supporting self-centered development and the second one, development through liberalization and opening up. In view of the economic decline of the region and the uncertainties brought about by the implementation of strategies developed from the above two models, this paper will investigate the following question: given the internal and external constraints and contradictions in the different economies in the region, how can one conceive the long-term development of Sub-Saharan Africa beyond strategies aimed at merely overcoming the crisis? Two rules should be observed regarding priorities to be selected and, hence, the orientation of development in the region. One, radical and exclusionary solutions such as total opening and specialization or introversion at any cost, ought to be avoided. One should instead implement "relative, selective protectionist" policies encouraging maximum use of opportunities created by the promotion of exports and survival of a number of vital areas that are protected from international competition. Two, one should always bear in mind that only activities that are first and foremost geared toward meeting the basic needs of the people and generating jobs should be selected. Secondly, in terms of regulating growth and the direction of the development process, one should beware Of peremptory moves consisting in systematically giving precedence to, either, private initiatives over public ones, or market over the State, or external competitivity over regional integration. It may be wiser to take into consideration the redes and functions of the different actors and make use of the advantages of the different regulation methods. Finally, in spite of the dominant practice of considering mobilization of resources as nothing else but fund raising and in the past few years, as the debt issue especially, one should keep in mind that people should be both the first resource to mobilize and the first beneficiaries of development Such a mobilization of people is only possible if it is integrated in a self-development strategy, that is, if the given people enjoy relative autonomy in defining objectives and in decision making.